2021
DOI: 10.1007/s10803-021-04906-z
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Gaze Behaviour of Children Diagnosed with Autism Spectrum Disorders in a Classroom Setting

Abstract: A defining feature of ASD is atypical gaze behaviour, however, eye-tracking studies in ‘real-world’ settings are limited, and the possibility of improving gaze behaviour for ASD children is largely unexplored. This study investigated gaze behaviour of ASD and typically developing (TD) children in their classroom setting. Eye-tracking technology was used to develop and pilot an operant training tool to positively reinforce typical gaze behaviour towards faces. Visual and statistical analyses of eye-tracking dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 53 publications
(75 reference statements)
1
13
1
Order By: Relevance
“…We found that autistics and neurotypicals did not differ in their overall social attention on their interactional partner’s eyes. This result contrasts with McParland et al (2021) who found less attention to faces in autistic children in comparison with neurotypicals, although this group effect was restricted to the contrast between dyadic versus triadic exchanges. At the same time, our results are in line with other live eye-tracking studies that found an overall comparable attention to the interlocutor (e.g., Nyström et al, 2017).…”
Section: Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“…We found that autistics and neurotypicals did not differ in their overall social attention on their interactional partner’s eyes. This result contrasts with McParland et al (2021) who found less attention to faces in autistic children in comparison with neurotypicals, although this group effect was restricted to the contrast between dyadic versus triadic exchanges. At the same time, our results are in line with other live eye-tracking studies that found an overall comparable attention to the interlocutor (e.g., Nyström et al, 2017).…”
Section: Discussioncontrasting
confidence: 96%
“…And yet, previous studies highlighted how important the experimental setting is. For instance, McParland et al (2021) found that, when discussing with adult partners in a classroom, neurotypical children tend to be more socially attentive during dyadic exchanges (an adult and the child) in comparison with triadic exchanges (two adults in addition to the child), a pattern opposite to that displayed by autistics. Similarly, Macari et al (2021) found that infants and toddlers later diagnosed as autistic displayed, as compared with nonautistics, a reduced social attention during dyadic bids.…”
Section: Lab Versus Live Paradigmsmentioning
confidence: 99%
“…Across typical development social attention and especially joint attention needs to be rapidly, consistently and frequently engaged in order to stay with the dynamic shifts of points of common reference and to maintain adaptive social attention coordination in group social interactions with peers, adults or in the classroom ( 41 , 48 , 185 ). The developmental increase in efficiency of execution of joint attention is illustrated by studies that indicate that the latency to respond to gaze shifts or joint attention bids decreases from about 3.25 s at 2-months, to about 1.5 s at 8-months ( 18 ), to about 0.80 s at 18-months ( 186 ), and finally to 0.67 s in adolescence ( 187 ).…”
Section: Motivation and Social Attention In Older Individualsmentioning
confidence: 99%
“…Modern research focuses on establishing intelligent classroom technologies with eye tracking and voice recording [114,89]. Those methods have their limitations due to the data security but deliver more insights and allow reducing the induced bias by humans [114,89,90].…”
Section: Gaze Based Group Behavior Researchmentioning
confidence: 99%